The post-Soviet as post-colonial : a new paradigm for understanding constitutional dynamics in the former Soviet empire /: a new paradigm for understanding constitutional dynamics in the former Soviet empire. (2022) - Partlett, William, 1979-; Küpper, Herbert, 1964-
No abstract available